Islamism and Gender Relations in the Muslim World as Reflected in Recent World Values Survey Data - Arno Tausch; Almas Heshmati (Institute for the Study of Labor (IZA), 2016)
Ever since Goldin (1995) proposed the idea that there is a U-shaped female labor force participation rate function in economic development, empirical research is stunned by the question why the countries of the Middle East and North Africa (MENA) are characterized by such low rates of female labor force participation. This gap in labor economics research is all the more perplexing since gender equality, particularly in education and employment, significantly contributes to economic growth. The research strategy of the present paper is within a relatively new tradition in labor market research, initiated by the recent article by Besamusca, Tijdens, Keune and Steinmetz (2015), which does not exclude anymore the "religious factor" and what these authors call "gender ideology". Our analysis of the "gender ideology" of Islamism and gender values is based on an empirical analysis of World Values Survey data. In recent economic theory, Carvalho (2013) maintained that Muslim veiling is a strategy for integration, enabling women to take up outside economic opportunities while preserving their reputation within the community. The empirical data clearly support a pessimistic view. We show that Muslim Feminism, which implies according to our data analysis the rejection of the twin brothers - Islamism and the veil - and the democracy movement in the Muslim world are closely interrelated. Thus, it is imperative that Western Feminism develops solidarity with Muslim Feminism, and that labor economics does not exclude anymore "the religious factor" from the analytical frameworks explaining low female labor force participation rates.
Keywords: A13; C43; F66; J15; J16; J21; J42; N30; Z12; 330; economics of gender; sociology of economics; comparative study; political economy; female labor participation; religion; social values; index numbers; factor analysis; World Values Survey